ANALISIS PREDIKSI KEBANGKRUTAN MENGGUNAKAN MODEL ALTMAN Z-SCORE PADA PERUSAHAAN RITEL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Rosmayana Rusman (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Bankruptcy is a critical issue that companies must be aware of. Bankruptcy and the level of the company's performance can be seen from the company's financial condition by analyzing the company's financial statements. The most widely used bankruptcy prediction model is the Altman Z-Score model..The Altman Z-Score model analysis was chosen as the model used in bankruptcy prediction because, this model is easy to use with a high degree of accuracy. The purpose of this research is to determine bankruptcy predictions using the Altman Z-Score model in retail companies listed on the IDX in 2014-2018. This kind of exploration is expressive quantitative utilizing monetary reports as an examination instrument. The examining method was,carried out by utilizing purposive sampling,technique which was then controlled by nine retail organizations as the sample. The results show that on average six companies are in a safe zone, including issuers ECII, HERO, MPPA, RANC, SKYB, SONA and two companies in the gray zone or prone to bankruptcy, namely CENT and KOIN, one company in the dangerous zone, namely RIMO